1999
DOI: 10.1002/(sici)1097-4628(19990711)73:2<149::aid-app2>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of highly porous poly(methacrylic-co-triethylene glycol dimethacrylate) by suspension polymerization

Abstract: Porous poly(methacrylic-co-triethyleneglycol dimethacrylate) (MAA-3G) was prepared by suspension polymerization using benzoyl peroxide as an initiator, poly(vinyl alcohol) as a protective colloid, and n-hexane as a porogenic agent. The prepared polymer was base hydrolysed using hydroxyl amine and sodium methoxide into the corresponding polyhydroxamic acid (HYOX). The metal binding behavior of polyhydroxamic acid with various metal ions, the effect of pH on the metal ion capturing, and the selectivity of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
(5 reference statements)
0
2
0
1
Order By: Relevance
“…Estudos sobre a natureza do diluente, o grau de diluição e o teor de agente reticulador foram feitos embasados também em determinações de propriedades porosas dos materiais 9,12,22,23,[43][44][45][46][47][48][49][50] . A partir daí, passou-se a utilizar tais conhecimentos para se obter materiais com características porosas definidas para uma dada aplicação 24,51,52 .…”
Section: Porosidade Em Copolímeros à Base De Divinilbenzenounclassified
“…Estudos sobre a natureza do diluente, o grau de diluição e o teor de agente reticulador foram feitos embasados também em determinações de propriedades porosas dos materiais 9,12,22,23,[43][44][45][46][47][48][49][50] . A partir daí, passou-se a utilizar tais conhecimentos para se obter materiais com características porosas definidas para uma dada aplicação 24,51,52 .…”
Section: Porosidade Em Copolímeros à Base De Divinilbenzenounclassified
“…Most ion exchange bead resins are manufactured by a suspension polymerization using styrene and divinylbenzene (DVB) 14, 15, 16. The DVB is a crosslinking agent which gives the beads their physical strength.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported details about the preparation of these resins using porogenic solvents 10, 11. As a consequence of our previously published work,12, 13 we prepared and characterized porous polyhydroxamic acid and a polyhydroxamic–metal catalyst, with a high surface area, by the seed emulsion polymerization technique.…”
Section: Introductionmentioning
confidence: 99%